What things do : Philosophical reflections on technology, agency, and design - Verbeek, Peter-Paul, 1970- (University Park, Pa. : Pennsylvania State University Press, 2005)
Focuses on how technologies mediate our actions and our world perceptions. Peter-Paul Verbeek examines the philosophy of technology formulated by Jaspers and Heidegger, and extends the work of more recent philosophers of technology. He shows how his "postphenomenological" approach applies to the technological practice of industrial designers
Technology and the self -- The thing about technology -- Postphenomenology -- A material hermeneutic -- The acts of artifacts -- Devices and the good life -- Artifacts in design
Includes bibliographical references (pages 237-242) and index
Translated from the Dutch
Keywords: Technology -- Philosophy